Atypische intrazerebrale Blutungen - Ätiologie und Akutmanagement = Atypical intracerebral hemorrhage - etiology and acute management - Purrucker, Jan; Steiner, Thorsten (Der Nervenarzt, 2019)
Acute management as well as establishing the etiology of an intracerebral hemorrhage is still a challenge for clinicians. The location of the intracerebral hemorrhage alone should not be used to determine the cause because atypically located hemorrhages can be caused by long-standing arterial hypertension and typically located hemorrhages can occur due to non-hypertensive causes. Besides discussing the classification of intracerebral hemorrhages, this article focuses on a diagnostic algorithm as well as the presentation of potential (rarer) causes of non-traumatic intracerebral hemorrhages. Furthermore, the acute treatment of intracerebral hemorrhage with respect to recent data on blood pressure management as well as the management of bleeding under oral anticoagulant treatment are described.